A Platform for Complementary Metal‐Oxide‐Semiconductor Compatible Plasmonics: High Plasmonic Quality Titanium Nitride Thin Films on Si (001) with a MgO Interlayer. Issue 7 (24th May 2021) - Ding, Kai; Fomra, Dhruv; Kvit, Alexander V.; Morkoç, Hadis; Kinsey, Nathaniel; Özgür, Ümit; Avrutin, Vitaliy
Abstract : Titanium nitride (TiN) is highly attractive for plasmonics and nanophotonics applications owing to its gold‐like but tunable optical properties. Its prodigious potential for plasmonics has been demonstrated on sapphire or bulk MgO. For a transformational impact, high optical quality TiN on Si is required instead, which would support the integration of nanophotonics with the complementary metal‐oxide‐semiconductor (CMOS) electronics. However, TiN grown on Si, even at elevated temperatures, lacks the optical quality needed, imposed by the large lattice mismatch between them. Here, a novel approach is reported wherein a thin MgO interlayer is inserted between TiN and Si. The improved crystalline quality enabled by MgO for TiN on Si(001) leads to a significant enhancement of the plasmonic figure of merit (FOM = − ε ′/ ε ″) from 2.0 to 2.5 at telecommunication wavelength (peak FOM of 2.8), which is comparable to the widely accepted ultimate FOM obtained on bulk MgO grown under similar conditions. The TiN/MgO/Si structure enables the hybrid‐plasmonic‐photonic waveguide platform with sufficiently low losses, and thus long propagation lengths, for nanophotonic devices while providing additional practical advantages such as serving as a self‐aligned robust etching mask. Thus, the much‐anticipated potential of TiN on Si platform for CMOS compatible plasmonics is brought closer to reality. Abstract : The insertion of a thin MgO interlayer for TiN on Si (001) leads to cube‐on‐cube epitaxy of TiN films on Si with significantly improved plasmonic quality. The TiN/MgO/Si structure enables access to the hybrid‐plasmonic‐photonic waveguide platform with sufficiently low losses, and thus long propagation lengths from microns to tens of micrometers, for realistic nanophotonic devices while providing additional practical advantages.